Analisis Fitokimia dan Aktivitas Antioksidan Daun Kopi Robusta (Coffea canephora) Berdasarkan Perbedaan Ketinggian Tempat Tumbuh - Nintowati, Purina; Solichatun, Solichatun; Suratman, Suratman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Robusta Coffee Leaves are known to have high antioxidants that can stabilize free radical attacks. Based on the height of the place where Robusta Coffee grows, it has different characteristics, including producing different qualities and flavors from one another. This study aims to determine the content of phytochemical compounds and the antioxidant activity of Robusta coffee leaves based on differences in the height of the place where it grows. The research method used was sampling at several heights including 511 masl, 434 masl, 354 masl, 204 masl, 122 masl, and laboratory research for phytochemical and antioxidant tests. Data analysis used the ANOVA, DMRT, and Bivariate correlation tests to determine the correlation between height and antioxidant activity. The results showed that all five heights contained alkaloid and flavonoid compounds. The highest inhibition of antioxidant activity was found at an altitude of 511 masl with a percentage of 61.89% ±8.08b, while the lowest inhibition of antioxidant activity was found at an altitude of 122 masl with a percentage of 31.92% ±7.38a. Antioxidant activity at all five altitudes is classified as a very strong antioxidant with an IC50 value <50. Altitude has a significant effect (P<0.05) on antioxidant inhibition. Altitude has a positive correlation with antioxidant activity.